Adverse event management in the TOURMALINE-MM3 study of post-transplant ixazomib maintenance in multiple myeloma - Kaiser, Martin; Beksaç, Meral; Gulbrandsen, Nina; Schjesvold, Fredrik; Hájek, Roman; Moreau, Philippe; de Arriba de la Fuente, Felipe; Mateos, María-Victoria; West, Sharon; Spencer, Andrew; Rajkumar, S Vincent; Suryanarayan, Kaveri; et al. (Annals of hematology, 2020)
The phase 3, double-blind, placebo-controlled TOURMALINE-MM3 study (NCT02181413) demonstrated improved progression-free survival with ixazomib maintenance versus placebo post autologous stem cell transplant (ASCT) in multiple myeloma patients. We report additional safety data from TOURMALINE-MM3 to inform adverse event (AE) management recommendations. Patients were randomized 3:2 to receive ixazomib (n = 395) or placebo (n = 261) on days 1, 8, and 15 of 28-day cycles for ~ 2 years or until progressive disease/toxicity. The initial 3-mg ixazomib dose was escalated to 4 mg in cycle 5, if tolerated in cycles 1-4. Safety was a secondary endpoint assessed in all treated patients; AEs were graded using Common Terminology Criteria for AEs v4.03. The rate of grade ≥ 3 AEs was higher in the ixazomib arm (19%) than in the placebo arm (5%), but the rate of discontinuation due to AEs was similar (7% vs. 5%). For AEs of clinical interest, rates were higher with ixazomib versus placebo: nausea 39% versus 15%, vomiting 27% versus 11%, diarrhea 35% versus 24%, thrombocytopenia 13% versus 3%, and peripheral neuropathy 19% versus 15%. However, the majority of events were low-grade, manageable with supportive therapy or dose reduction, and reversible, and did not result in discontinuation. There was no evidence of cumulative, long-term, or late-onset toxicity with ixazomib maintenance. Ixazomib is an efficacious and tolerable option for post-ASCT maintenance. AEs associated with ixazomib maintenance can be managed in the context of routine post-ASCT supportive care due to the limited additional toxicity. ClinicalTrials.gov NCT02181413.
Keywords: senioři; Glycine; Maintenance therapy; transplantace kmenových buněk; Multiple Myeloma; sloučeniny boru; Middle Aged; mužské pohlaví; Boron Compounds; míra přežití; Multiple myeloma; Silicates; Follow-Up Studies; následné studie; Safety; mnohočetný myelom; Disease-Free Survival; ženské pohlaví; Humans; Autografts; Stem Cell Transplantation; Survival Rate; silikáty; Ixazomib; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; glycin; autologní štěp; Female; Aged; Adverse events; přežití bez známek nemoci; lidé; Male